Model of AlGaN/GaN based on High Electron Mobility Transistors using SILVACO ATLAS™ - El-Yazami Chaimae; Bri Seddik; El Fadl Adiba (E3S Web of Conferences)
Since the introduction of semiconductors, the world has undergone numerous profound transformations during the past few decades. With advancements in technology, semiconductor products' performance requirements keep rising. Research on novel materials and device structures is required to meet the criteria. This research presents a novel GaN HEMT construction. The components of an AlGaN/GaN heterojunction HEMT are the drain, source and gate electrode. Since M. Asif Khan and his colleagues published the first AlGaN/GaN HEMT in 1993, a lot of HEMT structures have been reported by researchers; nevertheless, none of them contain three electrodes on distinct sides of the device. In this study, we constructed a 2DEG GaN HEMT and observed its features, including its drain current characteristics curves, Ion/Ioff ratio, and transconductance characteristics curves. Which were acquired from simulations carried out with Silvaco ATLAS™.